PENGARUH SKEPTISME PROFESIONAL, KOMPETENSI, PEMAHAMAN ATAS SISTEM PENGENDALIAN INTERN AUDITI DAN PERTIMBANGAN RISIKO AUDIT TERHADAP KEMAMPUAN PENDETEKSIAN KERUGIAN DAERAH PADA INSPEKTORAT PROVINSI SULAWESI UTARA - Popilo, Riyani Leady; Saerang, David Paul E.; Ilat, Ventje (JURNAL RISET AKUNTANSI DAN AUDITING "GOODWILL", 2016)
Inspectorate of North Sulawesi Province has a role to provide early warning and improve the effectiveness of risk management in implementing the tasks and functions of government agencies (anti corruption activities). This research aims to test the effect of professional scepticism, competence, the understanding of auditee internal control system and audit risk consideration to the ability of regional loss detection as simultaneous and partial in Inspectorate of North Sulawesi Province. The sample in this research is the 70 auditors. The variables that used are professional skepticism (X1), competence (X2), understanding of auditee internal control system (X3) and audit risk consideration (X4) as independent variables and ability of regional loss detection (Y)as dependent variable. This research use quantitative method with multiple regression analysis. The results indicate that professional skepticism, competence, understanding of auditee internal control system and audit risk consideration simultaneously have significant effect to the ability of regional loss detection. Partially,  professional skepticism and understanding of auditee internal control system have a significant effect to the ability of regional loss detection, whereas the competence and audit risk consideration have no significant effect to the ability of reginal loss detection. Keywords        :           regional loss, skepticism, competence, internal control system, audit risk